Prevention of Covid-19 transmission through the implementation of clean and healthy life patterns in school age children in PAUD, Tambak Boyo Village - Benny Karuniawati (Universitas Muhammadiyah Magelang, 2022)
In Tambak Boyo Village, school-aged children account for roughly 14% of the total population. The school years are an ideal time to instill the values of clean and healthy living (PHBS). Given that children will return to school in the new normal period, PHBS in schools feels even more important. The purpose of this service is to improve people's health by instilling a clean and healthy lifestyle in young children in order to prevent disease transmission, particularly the current epidemic, Covid-19, through hand washing and tooth brushing. The program's implementation methods begin with lecturing on the material, then demonstrating proper hand washing and tooth brushing to maintain oral health, and finally mentoring PAUD children as they practice hand washing and tooth brushing. The results of the activities carried out on 30 children revealed that 86.7 percent of them could wash their hands sequentially according to the five steps of handwashing, and 73.3 percent could brush their teeth properly.